2002
DOI: 10.1046/j.1365-2362.2002.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

PON1 L55M polymorphism is not a predictor of coronary atherosclerosis either alone or in combination with Q192R polymorphism in an Italian population

Abstract: These findings did not indicate a major effect of the PON1 L55M polymorphism, either alone or in combination with the Q192R polymorphism, on CAD risk. Additional studies are needed for a better evaluation of the role of the 55/192 PON1 genotypes in combination on myocardial infarction risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 36 publications
1
32
1
Order By: Relevance
“…(39) In addition, Blatter-Garin et al reported that homozygosity for the 55Leu allele of PON1 is an independent risk factor for CHD in non-insulin-dependent diabetics (44), which is supported by other studies (74, 128). In contrast, some studies conducted in patient groups of different ethnicities found no significant association between the 55 polymorphism and the presence of CHD (15,214,291,358).…”
Section: Pons Polymorphisms and Coronary Artery Diseasementioning
confidence: 81%
“…(39) In addition, Blatter-Garin et al reported that homozygosity for the 55Leu allele of PON1 is an independent risk factor for CHD in non-insulin-dependent diabetics (44), which is supported by other studies (74, 128). In contrast, some studies conducted in patient groups of different ethnicities found no significant association between the 55 polymorphism and the presence of CHD (15,214,291,358).…”
Section: Pons Polymorphisms and Coronary Artery Diseasementioning
confidence: 81%
“…The PON1 55 Leu and 192 Arg isoforms have been associated to an increased risk of CAD in some clinical studies [20-35], but not all [36][37][38][39][40][41][42][43][44][45][46][47][48][49]. This controversy was addressed by a recent metaanalysis including about 24 000 subjects [50], which showed no significant association between Leu55Met and CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The HDL particles from 55 Met/Met and 192 Gln/Gln individuals have been demonstrated to be most effective in protecting LDL from oxidative modification [19]. The alleles less effective in protecting from oxidative stress, 55 Leu and the 192 Arg, have been associated with an increased risk of vascular disease in some clinical studies [20- 35], but not all [36][37][38][39][40][41][42][43][44][45][46][47][48][49]. A recent meta-analysis showed no significant association between 55 Leu allele and coronary heart disease, whereas a weak, but statistically significant increased risk (OR=1.12 with 95% CI=1.07-1.16) was found for the 192 Arg allele [50].…”
Section: Introductionmentioning
confidence: 99%
“…Few case-control studies of the 55 polymorphism have been done. Some have shown an association between the PON1 55L allele and atherosclerosis 83,93 , but others have not 84,94 . However, no prospective studies of CAD and PON1 polymorphisms are available.…”
Section: Pon1 Coding Region Polymorphisms and Cadmentioning
confidence: 99%